2016
DOI: 10.3920/jiff2016.0028
|View full text |Cite
|
Sign up to set email alerts
|

Growth and survival of reared Cambodian field crickets (Teleogryllus testaceus) fed weeds, agricultural and food industry by-products

Abstract: This study evaluated survival and growth of Cambodian field crickets (Teleogryllus testaceus) during captivity when fed a set of local weed species, agricultural and food industry by-products. Wild individuals were caught at two locations in Cambodia, kept in pens and fed commercial chicken feed until the second generation off-spring hatched. First larval stage nymphs from this generation were collected and used in a 70-day feeding trial with one control treatment (chicken feed) and 12 experimental treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 16 publications
2
75
1
Order By: Relevance
“…Miech et al (2016) found that this species performs well on cassava plant tops, but also on several weeds, in particular Cleome rutidosperma.…”
Section: Reducing Organic Wastementioning
confidence: 99%
“…Miech et al (2016) found that this species performs well on cassava plant tops, but also on several weeds, in particular Cleome rutidosperma.…”
Section: Reducing Organic Wastementioning
confidence: 99%
“…For example, the FCR for larval stage Tenebrio molitor and nymphal stage Acheta domesticus ranges from 2.2 to 5.3 and from 1.6 to 4.5, respectively, depending on the diet and life stage. It is also clear from individual studies [27] and life cycle assessments (LCAs) [28,29] that the feed used for insect rearing plays a large role in the efficiency of them converting this into protein.…”
Section: Insects Are Efficient Feed Converters: Is That All We Need Tmentioning
confidence: 99%
“…Most studies with encouraging results regarding artificial diets based on food wastes or mixtures of wastes have been carried out using edible mealworm (Tenebrio molitor L., Coleoptera: Tenebrionidae), black soldier fly (Hermetia illucens, Diptera: Stratiomyidae), housefly (Musca domestica, Diptera: Muscidae), and Cambodian cricket (Teleogryllus testaceus, Orthoptera: Gryllidae) and have used raw food material as the insect feed [28,31,60,62,[64][65][66][67].…”
Section: Edible Insect Species That Can Utilize Food Waste As Feed Anmentioning
confidence: 99%
“…Farmed edible insects that utilize food materials and wastes during rearing are summarized in Table 2. Rice bran, cassava plant tops, water spinach, spent grain, residues from mungbean sprout production [67] In general, the major macronutrients required for insect mass production are (a) carbohydrates, which serve as an energy pool but are also required for configuration of chitin (exoskeleton of arthropods) [60], (b) lipids (mainly polyunsaturated fatty acids such as linoleic and linolenic), which are the main structural components of the cell membrane, and also store and supply metabolic energy during periods of sustained demands and help conserve water in the arthropod cuticle [29,59,69], and (c) the amino acids leucine, isoleucine, valine, threonine, lysine, arginine, methionine, histidine, phenylalanine, and tryptophan, which insects cannot synthesize [70], and tyrosine, proline, serine, cysteine, glycine, aspartic acid, and glutamic acid, which insects can synthesize, but in insufficient quantities at high energy consumption [61,70]. The essential micronutrients in insect rearing are (a) sterols, which insects cannot synthesize, (b) vitamins, and (c) minerals [30].…”
Section: Edible Insect Species That Can Utilize Food Waste As Feed Anmentioning
confidence: 99%
See 1 more Smart Citation